The Utilization of Text Summary Techniques to Improve Students’ Reading Comprehension Skills - Avivah, Avivah; Hilmiyati, Fitri; Khaeroni, Khaeroni (Journal of Integrated Elementary Education, 2022)
This study aims to improve students’ reading comprehension skills using the text summarization technique in the 5th grade of SDN Kasunyatan. The subjects of this classroom action research (CAR) involved forty students. The data was collected using learning observation, reading comprehension tests, and documentation. The analysis of these data uses both qualitative and quantitative descriptive approaches. This study uses a text summarization technique as an action. The text summarization technique has four syntaxes. First is monitoring, which means that students read the text until they understand the reading material. Next is trimming down to take keywords from each paragraph, then combining these keywords and creating mind mapping. The last is calling; it means that students rewrite all things they remember about the reading text. This research shows that the text summarization techniques improved students’ reading comprehension skills, indicating an increase for each indicator.